Manfaat Metode Pembelajaran Hypnoteaching Dalam Proses Belajar - Rahmi Fratiwi; Neviyarni S; Herman Nirwana (GLOBAL SCIENTS PUBLISHER, 2025)
The hypnoteaching learning method can provide benefits in the teaching and learning process in schools. In its implementation, the learning process using the hypnoteaching learning method can have quite an effective impact in helping to overcome difficulties, both difficulties faced by teachers and difficulties faced by students. By combining hypnosis techniques into the learning process and creating learning conditions that are more relaxed, focused, interesting and enjoyable, hypnoteaching can have the potential to significantly increase student learning achievement, concentration, reduced anxiety and higher learning motivation. Through a literature review, this research aims to reveal how hypnoteaching can facilitate students' understanding of subject matter and strengthen the relationship between teachers and students. It is hoped that the results of the study will provide a clearer picture of the benefits of hypnoteaching methods in the learning process for students at school.